Musical stage theory: a novel account for the ontology of musical works and the authenticity of music - Moruzzi, Caterina (2018)
Listening to music is one of the most common human activities. Yet, answering the question ‘What is a musical work?’ has kept many scholars busy. In this thesis, I present a novel account for the ontology of musical works: Musical Stage Theory. Traditional theories describe musical works as abstract entities, as Platonists claim, or as classes of performances, as in the Nominalist tradition. Musical Stage Theory, instead, argues that the work is the performance. Delineating this account will help me also in defending a contextualist interpretation of authenticity in musical performance. I propose this account as an alternative to mainstream and well accepted views on the nature of musical works with a specific intent: suggesting a way to analyse the identity of musical works which gives due relevance to musical practices and, at the same time, is grounded on a solid ontological basis. The original contribution brought by Musical Stage Theory is twofold: first, it gives promising prominence to the sonic/performative dimension which, in a sense, has remained as an afterthought in alternative theories. Second, it promotes an active collaboration between the disciplines of music and philosophy, supporting philosophical investigations with musicological considerations and case studies. In order to achieve this second goal, in the thesis I adopt a multivalent methodology. In addition to a more traditional philosophical approach, I support conceptual analysis with the results obtained from interviews conducted with musicians and theorists on their understanding of musical authenticity. After presenting the benefits of Musical Stage Theory against more traditional theories in the ontology of music, I apply its theoretical framework to actual musical phenomena and case studies, showing how Musical Stage Theory can change the way in which we approach the study and perception of music. I conclude with the proposal of a contextualist interpretation of the notion of authenticity in musical performance, justifying it on the basis of the nature of musical works as defended by Musical Stage Theory.